2012
DOI: 10.1159/000338575
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Injury in Mountaineering, Rock and Ice Climbing

Abstract: Climbing and mountaineering sports are gaining more and more public interest. This chapter reviews scientific studies on injuries and accidents in climbing and mountaineering sports to evaluate the danger of these sports and their specific injuries and preventive measures. An initial PubMed query was performed using the key words 'rock climbing', 'sport climbing', 'mountaineering', 'alpine injuries' and 'climbing injuries'. More than 500 extracted papers were analyzed which gave information on injury, mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
126
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(133 citation statements)
references
References 62 publications
4
126
2
1
Order By: Relevance
“…Neuhof et al [2] in contrast found a even injury distribution between the upper (42.6%) and lower extremities (41.3%) (Figure 1). In summary, most of the studies found that overuse injuries are mainly affecting the upper extremity, while acute traumatic injuries are more frequently located on the lower extremity [1,76] . Also, besides the acute lower limb injuries the incidence of chronic feet problems increases in the higher levels of sport climbing [23,25,75,77,78] .…”
Section: Et Al Feet Injuries In Rock Climbersmentioning
confidence: 96%
See 2 more Smart Citations
“…Neuhof et al [2] in contrast found a even injury distribution between the upper (42.6%) and lower extremities (41.3%) (Figure 1). In summary, most of the studies found that overuse injuries are mainly affecting the upper extremity, while acute traumatic injuries are more frequently located on the lower extremity [1,76] . Also, besides the acute lower limb injuries the incidence of chronic feet problems increases in the higher levels of sport climbing [23,25,75,77,78] .…”
Section: Et Al Feet Injuries In Rock Climbersmentioning
confidence: 96%
“…The literature data on injury distribution between the upper and lower extremity is inconsistent [1] . Many scientific climbing papers only present case studies or common hand injuries [17,19,30,41,48,54,55,[60][61][62][63] and are there- Table 1 The ten most frequent localization of climbing specific diagnoses 1/98-12/01 [61] n (%) Schöffl …”
Section: Injury Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6] Retrospective surveys have shed light on the nature and frequency of traumatic injuries sustained while climbing. [37][38][39][40][41][42][43][44][45][46] Advances in cervical spine management and immobilization, opiate-based pain control, and invasive procedures are being discussed. [47][48][49][50][51] Advanced techniques such as shoulder reduction are being taught to lay providers.…”
Section: Traumamentioning
confidence: 99%
“…Thus, understanding and accurately assessing the energy expenditure of diff erent types of physical activity is important for exercise prescription and for recommending the dose-dependent physical activity. While climbing and mountaineering sports are gaining more and more public interest [ 41 ] , most research concerning the energy cost of mountaineering has focused on high-altitude expeditions ( > 4 000 m) [ 30 ] , moderate altitude (2 500-3 800 m) [ 5 ] and rock climbing [ 14 ] . Low-intensity physical exercise in normobaric hypoxia (15 % O 2 , ≈ 2 500 m) leads to more weight loss in obese people than low-intensity physical exercise in normobaric sham hypoxia [ 33 ] .…”
mentioning
confidence: 99%